Optimalisasi Pengelolaan Obat dan Bahan Medis Habis Pakai (BMHP) melalui Edukasi Metode Fast Moving dan Slow Moving di RSUD Labuang Baji - Gemy Nastity Handayany; Achmad A. Aryl; Citra Nabila Athifah Al Basyirah (FKIP, Universitas Palangka Raya, 2026)
The management of medicines and Medical Consumables (MCs) plays a crucial role in improving the quality of pharmaceutical services in hospitals. Common problems include stock imbalances, such as shortages and overstocking, which negatively affect service efficiency, increase operational costs, and raise the risk of product expiration. These issues are often caused by inadequate planning that is not based on consumption data, as well as limited knowledge of pharmacy personnel in applying appropriate inventory control methods.This community service activity aimed to improve the knowledge and skills of pharmacy staff in managing inventory using fast moving and slow moving methods based on real hospital data. The implementation method consisted of education, training, and hands-on mentoring conducted in several stages. The activity began with the analysis of medicine and medical consumables usage data from January to December 2025 at Labuang Baji Regional General Hospital, followed by training on pharmaceutical logistics management, and continued with practical exercises on classification and inventory control. Evaluation was carried out through discussions, case studies, and observation of participants’ ability to apply the methods.The results showed that 50.7% of medicines and 52.4% of medical consumables were categorized as fast moving, while the remaining items were classified as slow moving. After the intervention, there was a significant improvement in participants’ understanding of inventory classification, stock turnover analysis, and data-based planning. Participants were also able to identify items at risk of stock-outs and overstocking, enabling more appropriate control measures.This activity had a positive impact on the efficiency of pharmaceutical inventory management, reduced the risk of stock-outs and overstocking, and supported the improvement of healthcare service quality. Therefore, the fast moving and slow moving methods can be considered effective and applicable approaches for data-driven pharmaceutical inventory management in hospital settings